Affective-sexual and gender diversity in Spanish education: a systematic literature review - Ortega-Sánchez, Delfín; Sanz de la Cal, Esther; Ibáñez Quintana, Jaime; Encabo-Fernández, Eduardo (Frontiers in Education, 2025)
IntroductionThe aim of this present work is to systematically compile, map, and review the scientific literature concerning education on affective-sexual and gender diversity, produced within the Spanish geographical context over the past decade (2013–2023). To this end, this systematic review offers an unprecedented and updated synthesis of the most prominent challenges and areas for improvement in Spain, for the purpose of identifying existing research gaps, as well as curricular and training needs in this transdisciplinary field.MethodsTo achieve this objective, the PRISMA guidelines are applied in the extraction and selection of indexed materials from two of the principal internationally renowned databases, namely the Web of Science Core Collection and Scopus. The analysis was facilitated through the use of bibliographic management software, as well as quantitative and qualitative data analysis tools.ResultsThe findings obtained address the research question pertaining to the factors influencing the construction of attitudes and representations concerning this type of diversity within formal educational settings. Furthermore, the benefits, limitations, and obstacles surrounding its curricular integration are examined. Various socio-demographic variables of both students and educators, such as age, gender, religious beliefs, teaching experience, personal and social experiences, school-driven initiatives, and the persistence of hegemonic gender representations emerge as explanatory factors linked to these attitudes and representations. Similarly, the visibility of diverse identities, social inclusion, and plurality are associated with the necessity for education geared toward democratic citizenship. The sensitivity of the content and its curricular invisibility, along with training deficiencies, lack of academic recognition, and the absence of specific protocols for preventing LGBTIQphobia are identified as the most prominent limitations or hurdles for the comprehensive promotion of education pertaining to affective-sexual and gender diversity across distinct educational stages.DiscussionInstances of discrimination, harassment, and both physical and symbolic violence against non-heteronormative groups, grounded in the sex-gender system and cis-heteronormativity, continue to be recognized by educators. In this vein, scientific literature underscores the significance of education concerning affective-sexual and gender diversity as a means to eradicate stereotypes and negative attitudes toward LGBTIQ+ individuals, thereby striving toward genuine equity.